Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd008081.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography (OCT) for detection of macular oedema in patients with diabetic retinopathy

Abstract: Optical coherence tomography (OCT) for detection of macular oedema in patients with diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 59 publications
0
81
0
9
Order By: Relevance
“…Despite attempts to implement an OCT-based classification of DME [24] , there has been no consensus on its use. A Cochrane review concluded that there is substantial disagreement between the OCT findings and CSME as defined by clinical examination [25] . Nevertheless the changing treatment paradigm of DME, where anti-VEGF agents are increasingly being used in the management of DME, demonstrates that OCT is an essential tool in the current management of this condition [26] .…”
Section: Optical Coherence Tomography Classificationmentioning
confidence: 99%
“…Despite attempts to implement an OCT-based classification of DME [24] , there has been no consensus on its use. A Cochrane review concluded that there is substantial disagreement between the OCT findings and CSME as defined by clinical examination [25] . Nevertheless the changing treatment paradigm of DME, where anti-VEGF agents are increasingly being used in the management of DME, demonstrates that OCT is an essential tool in the current management of this condition [26] .…”
Section: Optical Coherence Tomography Classificationmentioning
confidence: 99%
“…95 This applies to two studies of reticular pseudodrusen in AMD by Ueda-Arakawa and colleagues 97 and Smith and colleagues, 101 and to both studies of diabetic macular oedema, by Vusojevic and colleagues 98 and Waldstein and colleagues. 84 …”
Section: Summary Of Quality Assessment In Relation To Risks Of Biasmentioning
confidence: 95%
“…l Some studies included both eyes of patients in analyses, which (because of intrasubject correlations) may have led to underestimation of standard errors for sensitivity and specificity (and hence also underestimation of the width of the confidence intervals). 95 As there is no formally agreed approach for analysing such data in evidence syntheses, 95 the current review does not investigate their impact on the precision of diagnostic outcomes. However, such cases are clearly identified in the review and any inaccuracy of confidence intervals in these cases would not have markedly altered the review conclusions.…”
Section: Limitationsmentioning
confidence: 99%
“…За счёт тракционных сил на участках устойчивого витреоретинального при-крепления, которые располагаются у диска зри-тельного нерва и в макуле, нередко развивается кистозный макулярный отёк. В некоторых слу-чаях тангенциальная тракция утолщённой натя-нутой задней гиалоидной мембраны индуцирует очень плоскую субклиническую макулярную от-слойку сетчатки, что сопровождается стойким снижением зрения [52,56].…”
Section: патогенез диабетического макулярного отёкаunclassified